Carlos Castillo y Otto F. Bond, University of Chicago Spanish dictionary. Revisado por D. L. Canfield. University of Chicago Press, Chicago-London, 1972; 2a. ed., lix + 635 pp. - Williamson, Rodney (El Colegio de México, 1973)
Se reseñó: University of Chicago Spanish dictionary.